The Role of Denpasar Government in Supporting the Resources of Endek Fabric Creative Industry - Antari, Ni Putu Bayu Widhi; Jannah, Lina Miftahul (UI Scholars Hub, 2016)
This purpose of this research paper is to describe the role of the Denpasar City Government in supporting the resources of endek fabric creative industry. The Denpasar Government has done a number of policies/activities in supporting the resources of endek fabric creative industry. As a result, the Denpasar Government earned with Upakarti and Innovative Government Award nomination in 2012. Furthermore, one of their attempts was submitted in UNPSA Competition. Nevertheless, endek fabric industry still face several problems, namely the lack of weavers and the crisis of competitiveness of the endek fabric. This research utilizes several concepts, such as the role of the government in the Triple Helix Model, the resource endowment in regional development, and creative industry. The approach is of the study is the qualitative approach that utilize in-depth interviews and literature study. The result is that the Denpasar City Government plays the role as the regulator by formulating the Denpasar Local Regulation No. 6/2012 as a cornerstone of the endek industry development. Furthermore, the Denpasar City Government provided weaving tools and conducted eight activities/policies, such as training and exhibitions; suggestion for using endek products; holding Denpasar Festival and trade mission; promoting Endek Ambassador pageant; building Imperium Kumbasari and Denpasar Design Center; establishing Denpasar's Endek, Bordir, and Songket Association. The Denpasar City Government has provided the interaction space between university and business interaction spaces. On the other hand, the Denpasar City Government still cannot overcome the crisis faced by the weavers.